KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VIII SMP NEGERI 8 PADANG - Desi Tiara Putri; Irfani Basri (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACTThe purpose of this study is to describe the following matters. First, it describes the reading skills of students in class VIII of SMP Negeri 8 Padang. Second, describe the news writing skills of VIII students of SMP Negeri 8 Padang. Third, it describes the correlation between reading comprehension skills and news writing skills of eighth grade students of SMP Negeri 8 Padang. This type of research is quantitative research with descriptive methods. The results of this study are three. First, reading comprehension skills of eighth grade students of SMP Negeri 8 Padang are in good qualifications. This was concluded based on an average count of 81.13. Second, the writing skills of news texts for eighth grade students of SMP Negeri 8 Padang are in good qualifications. This can be seen from the acquisition of the average news text writing test count of 81.25. Third, there is a significant correlation between reading comprehension skills and news writing skills of VIII grade students of SMP Negeri 8 Padang at n-1 degrees of freedom and a significant level of 95%.  The null hypothesis is rejected and the work hypothesis is accepted because the test result prove the t value is greater than t table 3.81 > 1.68. Based on the result of the study above, it was concluded about the knowledge of reading skills in reading news texts of eight grade students of SMP Negeri 8 Padang.Kata Kunci: korelasi, membaca pemahaman, menulis teks berita